2021
DOI: 10.1080/25741292.2020.1864120
|View full text |Cite
|
Sign up to set email alerts
|

Gender and policy response to COVID-19 in Canada and Scotland

Abstract: Overcoming pandemics call for immediate and dedicated public health policy solutions. This study analyzes the public health policies introduced in the province of Ontario in Canada, and the country of Scotland in the United Kingdom, in a bid to address the COVID-19 pandemic. We focus on regional policy design by the key health policy decision makers and examine the influence of gender in the solutions introduced by these policy leaders. Drawing from the concept of feminist sociological institutionalism, we arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Reproductive tasks were exacerbated and increased during the pandemic and by the government’s lockdown measures. Additionally, during this period, a triple workload was generated: paid, domestic, and community work [ 35 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive tasks were exacerbated and increased during the pandemic and by the government’s lockdown measures. Additionally, during this period, a triple workload was generated: paid, domestic, and community work [ 35 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Canada and Scotland by Soremi et al [ 35 ] indicated that female political leaders do not need to base their legitimacy on gender, even more so in environments where these policies have already been institutionalized, adding that the emphasis should be on professional progress.…”
Section: Resultsmentioning
confidence: 99%
“… 2 Soremi and Dogo (2021, 147) are a recent exception, arguing that where the presence and leadership of women are ‘an accepted phenomenon’, ‘female policy leaders do not need to hinge their legitimacy on gender in designing policies’.…”
mentioning
confidence: 99%